Loyalty Influencers in Adolescents : Evidence from Emerging Markets - Shetty J., Swapna; P. G., Mahesh; K. K., Ganavi (Prabandhan: Indian Journal of Management, 2023)
Purpose : The major goal of this study was to improve the understanding of the factors that influence adolescent fashion clothing loyalty. While there was a considerable amount of research on this subject, it primarily focused on adult loyalty factors, with little attention paid to researching adolescent loyalty behaviors. Design/Methodology/Approach : The research adopted a quantitative methodology involving 446 participants. Data were collected among Indian adolescents through a meticulously designed structured questionnaire comprising of 21 items, each evaluated using a 5-point Likert scale. The research used the partial least squares (PLS) method to determine the selected constructs’ importance. Findings : According to the findings, brand sensitivity and the internet impacted satisfaction and brand loyalty. In contrast, socialization had an effect on brand loyalty rather than enjoyment. Research Implications : The research implications of this study could include insights for marketers targeting adolescent consumers, suggesting the importance of brand sensitivity and the Internet in fostering loyalty. Additionally, the findings regarding socialization’s impact solely on brand loyalty could affect how peer influence affected consumer behavior. Originality/Value : The originality and value of this research lay in its exploration of adolescent loyalty factors often overlooked in previous studies. By incorporating multiple elements and mediating factors, this study contributed to a deeper understanding of how adolescents develop loyalty toward fashion apparel brands.